Improving Employment Through Interpersonal Psychotherapy: A Case Series of Patients With Treatment-Refractory Depression - Katagiri, Takeshi; Takaesu, Yoshikazu; Kurihara, Mariko; Oe, Yuki; Ishii, Miho; Onoda, Naoko; Hayasaka, Tomonari; Kanda, Yuta; Imamura, Yayoi; Watanabe, Koichiro (Frontiers in Psychiatry, 2021)
Patients with treatment-refractory depression (TRD) have significantly great losses in work productivity and employment. Interpersonal psychotherapy (IPT) is considered an approach for the treatment of TRD. However, the effectiveness of IPT in patients with TRD remains unclear. In this study, we report cases of TRD patients who underwent IPT after a detailed evaluation, along with their employment status. Of 112 patients who experienced one-week examination administration for TRD at Kyorin University Hospital, which aimed to determine appropriate diagnosis and treatment approaches for each patient, four patients who met the criteria for major depressive disorder according to DSM-IV-TR and were determined suitable for IPT were included in this report. Two patients had moderate, one had mild, and one had remission levels of depressive symptoms according to the Montgomery-Asberg Depression Rating Scale at the time of admission. All four patients completed the scheduled sessions of IPT (6–16 sessions) in the outpatient clinic and achieved remission. All four patients attained full-time employment within six months after receiving IPT. This study suggests that the appropriate selection of IPT might be effective for TRD patients, possibly leading to positive outcomes, including work productivity and employment status.